RACISM AS POLITICAL WEAPON AND NOT SOCIAL BEHAVIOR BASED ON VIKAS SWARUP'S “Q&A" - Dedy Fauriza Rosyadi (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Racism is the basic problem of the human diversity in the world. It is the treatment that influenced by the distinctive of physical characters combination which the pattern of ethnic relation such us skin colour, hair, shape nose, eye, and etc. Thus, this research intends to examine the racism pattern which appears in two novels of Vika Swarup as Indian, they are Q&A and Six Suspects. In order to examine the racism pattern, this work proposed: (1) how is racism depicted in the Q&A and Six Suspects novel. (2) what the goals of racism do in the world. (3) how do the ethnic pattern change the social life.The pattern of racisms is analyzed in accordance with theory which proposed by Horton and Hunt. This work’s result shows that the pattern of racism which are depicted in both novels are annihilation, expulsion, partition, and segregation in which suggest that the racism is resulting from the relation between Muslims India (Pakistani) and Hindus as the dominant ethnic. Moreover, the effect of those racism pattern causing the minority reaction toward the dominant group. Individual attitude and social behavior are being the effect of the ethnic pattern change in the social life.